Sosialisasi Wisata Dan Umkm Berbasis (FGD) Focus Group Discussion Guna Meningkatkan Kualitas Ekonomi Masyarakat Desa Jarak Kecamatan Wonosalam Kabupaten Jombang - Savira Apriliana; Niniek Imaningsih; Cholid Fadil (Fakultas Hukum, UPN Veteran Jawa Timur, 2022)
The center of the village community's economy to meet basic needs does not focus. Jarak Village, Wonosalam District, Jombang. The village which still has a lot of plantation land with its location at one of the foot of Mount Anjasmoro has beautiful views. In addition, this village also has superior tourism that has not been maximized due to access and support areas such as supermarkets and the lack of MSMEs. Utilization and development of tourism supported by the development of MSMEs can encourage the improvement of the economy of the surrounding community so that they can maximize the economy and reduce poverty levels. So it is necessary to hold socialization in order to increase public knowledge regarding tourism and MSMEs in order to increase the potential of the region and estuary will improve the village economy, especially the community,